8z+4-3z=44-3z

Simple and best practice solution for 8z+4-3z=44-3z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8z+4-3z=44-3z equation:


Simplifying
8z + 4 + -3z = 44 + -3z

Reorder the terms:
4 + 8z + -3z = 44 + -3z

Combine like terms: 8z + -3z = 5z
4 + 5z = 44 + -3z

Solving
4 + 5z = 44 + -3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '3z' to each side of the equation.
4 + 5z + 3z = 44 + -3z + 3z

Combine like terms: 5z + 3z = 8z
4 + 8z = 44 + -3z + 3z

Combine like terms: -3z + 3z = 0
4 + 8z = 44 + 0
4 + 8z = 44

Add '-4' to each side of the equation.
4 + -4 + 8z = 44 + -4

Combine like terms: 4 + -4 = 0
0 + 8z = 44 + -4
8z = 44 + -4

Combine like terms: 44 + -4 = 40
8z = 40

Divide each side by '8'.
z = 5

Simplifying
z = 5

See similar equations:

| x^4+x^2-14x-8=0 | | x^4+15x^2=0 | | 9x-11=5x+9 | | 20x^2-21x+4.5= | | 2(x+3)=-16 | | 8x-2=20-5x | | (2x+3)(2x+3)=49 | | -5c+3d-3c+8-d= | | -5i(6-4i)= | | 8x-2=10+3x | | (2x+3)2=49 | | 2(3-x)=10-(x+1) | | (7+2i)-(-4-i)= | | 15x^2+10x^2=0 | | x+0.44444444444=0.75 | | x+0.4=0.75 | | 4.25+3.5g=11 | | 4.25x+3.5=11 | | h=38-3t-5t^2 | | y=(9x+5)*4 | | y=9x+5*4 | | 3.25p-81=1.25 | | 3.25+1.25p=81 | | 16x^3+4x^2=0 | | x^2+3y^2-8x+4y-2=0 | | 3.25p+1.25=81 | | 16x^3-4x^2=0 | | 34x+4567=56x-210 | | 34x+4567=56x | | 9x(x+3y+4z)= | | 5(7x+9)=-130 | | 2x^2=2500 |

Equations solver categories